Identification Student’s Misconceptions on Hydrocarbon Material Using Four Tier Diagnostic Instrument - Sandi Danar Cynthia Sari; Muna Zhafirah, Alya; Kissya Rintyaningtyas, Patricia Putri; Fadlan Ramadhan, Muhammad; Amelia Halizsyah, Sabrina; Azha Hukmia, Siti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
Chemistry is a science that studies a deep understanding of something abstract and complex so in studying chemistry there are often many misconceptions. Hydrocarbon material is one of the topics in chemistry that requires a deep understanding therefore, misconceptions about hydrocarbon material have a high percentage of possibility. Misconceptions in basic materials have a sustainable impact thus, the author conducted a study by analyzing the misconceptions of students of SMA NEGERI 6 Kota Serang on hydrocarbon material, This study aims to identify the level of student understanding of hydrocarbon material and the causes of misconceptions in students. This study uses a quantitative descriptive method with an instrument in the form of a four-tier multiple- choice diagnostic test. The number of samples used in this study was 37 students who were class XI students majoring in chemistry. Data were obtained by giving questions in the form of a diagnostic test of 15 questions and a questionnaire to students. After being analyzed, data was obtained on students who understood the concept 26%, had misconceptions 41%, and did not understand the concept 33%. The factors causing misconceptions are that hydrocarbons have an abstract and complex concept (1), learning methods that are less effective in conveying concepts (2), a lack of interesting and interactive learning media (3), and assessments that only focus on memorization and do not measure students' understanding of concepts periodically.